2020
DOI: 10.3390/jcm9010141
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Clinical Trial: Calorie Restriction Regimen with Tomato Juice Supplementation Ameliorates Oxidative Stress and Preserves a Proper Immune Surveillance Modulating Mitochondrial Bioenergetics of T-Lymphocytes in Obese Children Affected by Non-Alcoholic Fatty Liver Disease (NAFLD)

Abstract: Fatty liver disease is a serious complication of childhood obesity. Calorie-restricted regimen (RCR) is one of the effective therapy for this condition. Aim of the study was to evaluate the effect of lycopene-rich tomato sauce with oregano and basil extracts in obese children with fatty liver on RCR. 61 obese children with fatty liver were enrolled, 52 completed the study. A randomized cross over clinical trial was performed. Participants were assigned to RCR alone or with a supplement of lycopene-rich tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Several clinical trials have proceeded in recent years to better verify the effects of plant-based foods, such as fruits, spices, and teas on NAFLD. A randomized cross-over clinical trial based on 61 obese children with NAFLD proved that daily consumption of 100 mL of tomato juice for 60 days could improve hepatic steatosis, insulin resistance, levels of leptin, and lipid profiles [ 156 ]. Additionally, a clinical trial found that in 55 patients, a 24-week intake of 36 g per day of dried grapes was beneficial for the prevention and management of NAFLD [ 157 ].…”
Section: Clinical Trials Of Plant-based Foods and Their Bioactive mentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have proceeded in recent years to better verify the effects of plant-based foods, such as fruits, spices, and teas on NAFLD. A randomized cross-over clinical trial based on 61 obese children with NAFLD proved that daily consumption of 100 mL of tomato juice for 60 days could improve hepatic steatosis, insulin resistance, levels of leptin, and lipid profiles [ 156 ]. Additionally, a clinical trial found that in 55 patients, a 24-week intake of 36 g per day of dried grapes was beneficial for the prevention and management of NAFLD [ 157 ].…”
Section: Clinical Trials Of Plant-based Foods and Their Bioactive mentioning
confidence: 99%
“…Further, in a repeated-dose toxicity test, after oral administrating tomato oleoresin at a dose of 4,500 mg/kg per day (which was equal to 325 mg/kg/day of (Z)-lycopene) for 4 weeks, the Wistar rats showed no adverse changes [ 186 ]. Only a few studies tried to use lycopene as a potential treatment against FLD with no adverse effects reported so that more evidence is needed on the topic [ 156 ].…”
Section: Safety and Application Issues Of Plant-based Foods And Thmentioning
confidence: 99%
“…Nobili et al [ 80 ] found that oxidative stress is highly prevalent in pediatric NAFLD. Reductions in oxidative stress parameters have been observed in clinical trials in children with NAFLD after treatment with vitamin E plus hydroxytyrosol [ 81 ], calorie restriction with lycopene-rich tomato juice supplementation [ 82 ], and n-3 PUFA supplementation [ 83 ]. Furthermore, lipid oxidation products (LPOs) such as 4-hydroxynonenal and malondialdehyde are produced as a result of the interaction between reactive oxygen species (ROS) and PUFAs derived from membrane phospholipids [ 84 ].…”
Section: Mitochondrial Dysfunction and Oxidative Stress In The Promentioning
confidence: 99%
“…Both acute and chronic calorie-restricted diets with either a low-fat or low-carbohydrate content are associated with reduced liver fat in patients with obesity [ 93 , 94 ]. Hypocaloric diets are also effective in improving NAFLD in patients with diabetes and children with obesity [ 95 , 96 ]. In experimental models, calorie restriction extends lifespan and reduces the hepatic steatosis associated with obesity [ 92 , 97 , 98 ].…”
Section: Introductionmentioning
confidence: 99%